University Teknologi Malaysia student accounting system / Rosni Md Nor and Saizah Abdul Rahman - Md Nor, Rosni; Abdul Rahman, Saizah (Faculty of Computer and Mathematical Sciences, 1979)
This report is about our training at University of Technology Malaysia. Duration is from 2nd December to February 1979.